Methods for Measurement of Solid Particles in Hydrocarbon Flow Streams - Nabipour, Amin; Evans, Brian; Sarmadivaleh, Mohammad; Kalli, C. (SPE International, 2012)
Sand production is one of the more critical issues causing delays and high costs to the petroleum production industry. To measure solid production in the hydrocarbon stream a number of sand monitors have been developed. Such monitors are installed in the flow line and are intended to provide information such as the onset of solid production or the amount of produced solids. Most sand monitors are based on the measurement of erosion due to impingement of sand particles or measuring ultrasonic signals generated by particle impacts on the pipe wall or piezoelectric elements. Having described the principal behind available monitors in the industry, capabilities and limitation of each type is explained in Part 1. Part 2 is comprised of a literature review carried out on the techniques which have the potential to be utilised in new generations of solids monitors. The principles of such methods as well as their advantages and disadvantages for solids monitoring applications are mentioned. In Part 3 subjects such as improving the data quality and data interpretation of current techniques, integration of available techniques into a single piece of equipment, and ranking of the most promising cases which are worthy of further investigation are discussed.